PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP TINGKAT KEUNTUNGAN PENGUSAHA KAYU DI KOTA BAUBAU - Ajo, Antasalam; Harudin, La Ode Muhammad (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2019)
To human beings, wood is a significant forest material. Without wood, people will have difficulties in meeting the living needs of wood and its production to have economic and sustainable quality. The goal of the analysis was to determine, partially and simultaneously, the effect of resources, the number of workers, the length of business and fuel on the profitability of wood-makers in the City of Baubau. The data obtained were analyzed with several linear regression equations T testing and F testing to measure the effect. The results showed that capital has a positive and significant impact on entrepreneurs ' income rates so that capital availability is very important. While the number of workers, the duration and the fuel volumes do not affect the profitability of wood entrepreneurs, the three variables were not taken into account as the main factors in increasing levels of profits. At the same time, the profitability of timber contractors did not affect resources, the number of employees, the duration of business and the amount of fuel. Adjusted R2 by 0.375 means that only 37.5% of the wood contractor's income is influenced by the factors measured in the report.   Keywords: Processed wood, forest products, profits